A Little Princess [Malá princezná anglicky] - Burnett, Frances Hodgson, 1849-1924 (Best of children´s classics, 2022)
I pretend I am a princess, so that I can try and behave like one.”When the kind and imaginative seven-year-old Sara Crewe reaches Miss Minchin’ s Select Seminary for Young Ladies with her papa, she doesn’ t quite like it.“ I don’ t like it, papa,” she said. “ But thenI dare say soldiers even brave ones don’ t really like going into battle.”The apple of her father’ s eye, Sara has all the privileges at the seminary and is treated with special care. Soon enough, she befriends her classmates and is nicknamed a ‘ princess’ , which she often pretends to be.But just after her eleventh birthday, when the news of her father’ s death arrives, everything changes. Will Sara Crewe's imagination help hercope up with the loss and hardships?One of the all-time children’ s novels, Frances Hodgson Burnett’ s A Little Princess is a remarkable story. It has been adapted for films, theatre, musicals, and television, and continues to remain popular more than a century after its publication.